2016
DOI: 10.3390/en9110954
|View full text |Cite
|
Sign up to set email alerts
|

Study on Insulator Flashover Voltage Gradient Correction Considering Soluble Pollution Constituents

Abstract: Natural polluted insulator surfaces are always coated with various kinds of soluble constituents, and those constituents affect flashover performance differentially. Currently, this fact is not considered either in laboratory experiments or field pollution degree measurements, causing the existing insulation selection method to be deficient. In this paper, a systematic study on insulator flashover voltage gradient correction involving different types of soluble pollution constituents is presented. Using a typi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Based on Table 6, discharge parameters N and n vary with the insoluble amount: both N and n decrease with NSDD. The results are in accordance with the results observed in [8,34] and confirmed by [11,17]. This can be related to the effect of the pollution constituent on the discharge temperature, as proposed in [8,27].…”
Section: Estimation Of Discharge Parameterssupporting
confidence: 91%
See 2 more Smart Citations
“…Based on Table 6, discharge parameters N and n vary with the insoluble amount: both N and n decrease with NSDD. The results are in accordance with the results observed in [8,34] and confirmed by [11,17]. This can be related to the effect of the pollution constituent on the discharge temperature, as proposed in [8,27].…”
Section: Estimation Of Discharge Parameterssupporting
confidence: 91%
“…By combining ( 5) and (10), it yields (11) Equation (11) shows that the flashover voltage depends on the pollution level, form factor, NSDD amount, and arc characteristics.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical constituents of pollution deposited on the insulator surface also affect flashover performance. [6] concluded that the flashover voltage of outdoor insulators depends on the soluble substance, their type and chemical composition. Daochun, et al [7] reported that Non-Soluble Salt Deposit Density (NSDD) also have an impact on flashover characteristics and in the slurry the size of particles in nonsoluble material is the primary reason affecting flashover.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in transmission line voltages and increased distance of renewable power sources from the loads, the importance of research on the pollution performance of insulators has significantly increased. The mechanism of flashover in high voltage porcelain, glass, and ceramic insulators under contamination has been studied extensively in the past [14][15][16]. Many researchers have proposed mathematical models to predict the critical flashover voltage under uniform and non-uniform pollution [17,18].…”
Section: Introductionmentioning
confidence: 99%